TOMPA SEBAGAI PENCIPTA ALAM: Memperjumpakan Konsep Allah Di Dalam Alkitab Pada Masyarakat Suku Dayak Kerambay - Christofer Juan Augusto; David Eko Setiawan (Jurnal Kala Nea, 2025)
This research is based on the problem of the lack of a contextual approach in proclaiming the Gospel to the indigenous Dayak Kerambay community, which often positions local culture as something that contradicts the Christian faith. As a result, the message of the Gospel is frequently difficult to accept and less relevant in the context of the local community’s life. The purpose of this study is to analyze the concept of Tompo in Dayak Kerambay beliefs and to bring it into dialogue with the biblical concept of God as Creator as a form of Christian theological contextualization. The research method used is descriptive qualitative research with a theological-contextual approach, conducted through literature review, analysis of biblical texts, and examination of the cultural understanding and local beliefs of the Dayak Kerambay community. The results of the study show that the concept of Tompo can be theologically reinterpreted as a means of introducing God as the true Creator without negating local cultural identity. This approach has proven effective in bridging the Christian faith with local culture, strengthening the acceptance of the Gospel, and encouraging the church to view culture as part of God’s saving work in human history. Thus, contextualization becomes an important strategy in presenting a Gospel that is relevant, transformative, and faithful to its essence.